Ohio Beyond the Mean: Socioeconomic Inequality in Body Mass Index Among Adults 2008-2021 - Kelly Balistreri; Rachael Ioele (Ohio Journal of Public Health, 2024)
Background: Obesity is a serious public health problem in Ohio. This study evaluated the heterogeneous relationship between socioeconomic status (SES) and body mass index (BMI) across the BMI distribution and examined the evolution of the gradient across time. Methods: The analyses were conducted using data from the 2008 Ohio Family Health Survey (OFHS) and the 2021 Ohio Medicaid Assessment Survey (OMAS). These surveys are repeated cross-sectional random probability samples of noninstitutionalized adults used to monitor the health and well-being of residential Ohioans. The sample consists of nonpregnant adults aged 19 years and older. Results: The change in BMI between 2008 and 2021 was most dramatic for women, with the entire distribution shifting to the higher range of values with the largest percentage change occurring at the 75th and 90th percentiles. The results showed a persistent educational and income gradient in BMI especially among women. While the income gradient is steepest at higher levels of BMI, the main impact of educational attainment occurs around the median BMI. The difference across the BMI distribution between those with and without a 4-year degree is most striking among women. Conclusion: Overall, women experienced the most significant shift in BMI compared to men. However, rates of BMI vary across socioeconomic indicators, with educational attainment having the greatest impact on BMI.
Keywords: Body mass index; Obesity; Health disparities; Socioeconomic inequality; Unconditional quantile regression